The fraction of an action is more than a movement: Neural signatures of event segmentation in fMRI - Schubotz, Ricarda I.; Korb, Franziska M.; Schiffer, Anne-Marike; Stadler, Waltraud; von Cramon, D. Yves (NeuroImage (Orlando, Fla.), 2012)
When we observe an action, we recognize meaningful action steps that help us to predict probable upcoming action steps. This segmentation of observed actions, or more generally events, has been proposed to rely in part on changes in motion features. However, segmentation of actions, in contrast to meaningless movements, may exploit additional information such as action knowledge. The present fMRI study sought to tear apart the neural signatures of processing two sources of information that observers may exploit at action boundaries: change in motion dynamics and action knowledge. To this end, subjects performed a segmentation task on both actions (that can be segmented based on motion and action knowledge) as well as tai chi movements (that can be segmented only based on motion) and two further control conditions that implemented point-light walker like displays of the same videos. Behavioral tests showed that motion features played a critical role in boundary detection in all conditions. Consistent with this finding, activity in area MT was enhanced during boundary detection in all conditions, but importantly, this effect was not stronger for actions. In contrast, only action boundary detection was reflected by specific activation in the superior frontal sulcus, parietal angular gyrus and the parahippocampal cortex. Based on these findings, we propose that during action observation, motion features trigger a top–down modulation of the attentional focus and the incitement of retrieving long-term memory place-action associations. While action perception entails activity common to processing of all motion stimuli, it is at the same time unique as it allows long-term memory based predictions of succeeding steps.